Molecular Techniques for Detection of Candida Species - Mohammed Harmal, Nabil Saad (2011)
Candida species are a major cause of invasive infections, in both critically ill and immunocompromised patients. Thus, rapid identification of these pathogens may facilitate specific therapy and patient management. The development of rapid and specific diagnostic methods remains a challenge. Different methods for the detection of Candida species including simplex and multiplex PCRs, PCR/RLB (Reverse Line Blot) hybridization technique, and finally a novel pan-fungal (yeast) specific primers for the detection of medically important Candida species and other fungal yeasts have been developed in this study. ATCC strains of Candida species (n=13), Aspergillus species (n=4), Pichia species (n=1), and two clinical isolates of Cryptococcus species were used in this study to confirm the specificity of the designed primers. For evaluation of the developed simplex and multiplex PCRs and PCR/RLB, 23 clinical strains of the following Candida species; C. albicans (n=5), C. glabrata (n=5), C. parapsilosis (n=5),and C. tropicalis (n=8) obtained from University Malaya Medical Centre (UMMC)between 2003 and 2004 were used (Table 3.2). In addition, 44 blood samples taken from BacT/Alert blood culture bottles were obtained from UMMC during the period from December 2009 to August 2010 were used for further validation. Simplex and multiplex PCR methods were developed for the detection of the four most common Candida species isolated from clinical samples: C. albicans, C. glabrata, C. parapsilosis, and C. tropicalis. The developed methods target the phospholipase B gene (PLB) as a novel target. The alignment software surprisingly showed that this gene contain large sequence variation among Candida species. The nucleotide sequence variability between C. tropicalis and C. glabrata was as high as 75%. Four pairs of species-specific primers were designed for the corresponding Candida species and used in the simplex PCR. New primer sets were designed for multiplexing purpose for C.albicans, C. parapsilosis, and forward primer for C. glabrata. While the reverse primer of C. glabrata and primer site of C. tropicalis used in the simplex PCR were also suitable for the multiplex PCR. On the other hand, novel species-specific primers and probes were designed for the development of specific PCR and PCR/RLB hybridization techniques for the detection of the less commonly isolated Candida species, namely; (C. famata, C. guilliermondii, C. lusitaniae, C. metapsilosis, and C. orthopsilosis). The methods developed targeted the internal transcribed spacer (ITS) region. The validity tests showed that the designed primers and probes achieved highly specific identification of the selected species, with no cross- reaction with the other tested fungal species. The methods were able to detect <10 cell/ml of culture broth when tested repeatedly for the corresponding Candida species. Finally a novel set of pan-fungal (yeasts) specific primers for the detection of medically important Candida species and other fungal yeasts were developed, by first amplifying DNA from Candida species, and other yeasts using the random amplified polymorphic DNA (RAPD) technique with arbitrary primers. A 550-bp PCR product, amplified with primers OPA-03 and NS-2 and common to Candida species and the other yeast, was selected for further evaluation. The fragment was cloned and subsequently sequenced. Based on the sequence data, two primers were selected and synthesized. The primer pair amplified a single fragment of 340 bp from DNA of Candida species and the other yeast. No amplification product was detected in DNA from Aspergillus species,bacteria, and human. This assay thus allows the precise and rapid detection of Candida species and other yeasts like Cryptococcus species.In conclusion, the results showed that the developed methods could be used for the rapid, specific and sensitive detection of both the most and less commonly encountered Candida species from the clinical specimens using the simplex/multiplex PCRs and PCR/RLB hybridization techniques, respectively. In addition, the pan-Candida/yeasts PCR developed in this study enables wide range detection of Candida species and other medically important yeasts like Cryptococcus species.